EXPLORING THE INTERSECTION BETWEEN NATURE AND MATHEMATICS IN HIGH SCHOOL: AN INTERDISCIPLINARY APPROACH TO PROMOTE SUSTAINABILITY AT THE STATE SCHOOL PROFESSORA MIRTES ROSAS MENDES DE MENDONÇA LIMA - Ney de Lima dos Santos, Nora; Letícia Freitas Bruce, Ana; Eloyse Santeiro Lima, Luany; de Medeiros Bruce, Natacha; Lucas Correa Potiguara, Vitor (Journal of Interdisciplinary Debates, 2025)
The paper entitled “Exploring the intersection between nature and mathematics in high school” presents an educational project developed at Escola Estadual Professora Mirtes Rosas Mendes de Mendonça Lima, which aims to integrate mathematical concepts with environmental issues. Using active methodologies such as the flipped classroom and design thinking, the project promotes environmental awareness among students, encouraging them to identify and analyze local problems, such as water waste and waste generation. Students not only learn to apply mathematical concepts in real contexts, but also develop critical skills and a sense of responsibility towards the environment, culminating in the creation of infographics that summarize their findings.